Psychological Capital's impact on the leadership-organizational climate preference relationship in potential leaders ∼ A study comparing teachers and sportsmen∼. Issue 5 (May 2022) - Wu, Mingchang; Kader Cassim, Farhad Abdul; Priambodo, Anung; Ko, Chenju
Abstract: Previous studies have demonstrated to some extent that the psychological capital of employees affects how they respond differently to leadership and organizational climate, but research has yet to investigate this in leaders, whether existing or potential. Studies in this area have also not made comparisons across occupational contexts. Hence, this research was initiated. The participants of our study consisted of 42 pre-tertiary teachers and 112 sportsmen nominated as potential future leaders, with the small group size of teachers being due to the more reserved tendency of their current leaders to elect fewer potential future leaders. The results of the study's survey confirmed the moderating influence of perceived psychological capital on the relationship between leadership style preference and organizational climate preference. However, under the moderating influence of perceived psychological capital, leadership style preference tended to influence organizational climate preference for the teachers while the opposite was the case for the sportsmen, indicating the possible influence of occupational culture. Highlights: Leadership and organizational climate influence each other. The direction of the influence may be impacted on by occupational setting and psychological capital. 42 pre-tertiary teachers and 112 sportsmen seen as potential future leaders were compared. Psychological capital and occupational setting were indeed found to affect the direction of the influence. Abstract : Leadership style preference (LSP), Organizational climate preference (OCP), Perceived psychological capital (PC), Potential future leaders.